Enhanced Dopamine D1 and BDNF Signaling in the Adult Dorsal Striatum but not Nucleus Accumbens of Prenatal Cocaine Treated Mice - Tropea, Thomas F.; Daruwalla, Zeeba R.; Kaur, Gagandeep; Rajadhyaksha, Anjali M.; Kosofsky, Barry e. (Frontiers in Psychiatry, 2011)
Previous work from our group and others utilizing animal models have demonstrated long lasting structural and functional alterations in the meso-cortico-striatal dopamine pathway following prenatal cocaine treatment. We have shown that prenatal cocaine treatment results in augmented D1 -induced cyclic AMP (cAMP) and cocaine-induced immediate-early gene expression in the striatum of adult mice. In this study we further examined basal as well as cocaine or D1-induced activation of a set of molecules known to be mediators of neuronal plasticity following psychostimulant treatment, with emphasis in the dorsal striatum (Str) and nucleus accumbens (NAc) of adult mice exposed to cocaine in utero. Basally, in the striatum of prenatal cocaine treated (PCOC) mice there were significantly higher levels of a number of the transcription factors studied. Following acute administration of cocaine (15 mg/kg, i.p.) or D1 agonist (SKF 82958; 1 mg/kg, i.p.) there were significantly higher levels of Ser133 P-CREB, Thr34 P-DARPP-32, and Thr202/Tyr204 P-ERK2 in the Str, that were significantly augmented in PCOC mice. In sharp contrast, in the NAc of those mice, we found increased P-CREB and P-ERK2 in PSAL mice, a response that was not evident in PCOC mice. Examination of Ser 845 P-GluA1 revealed increased levels in PSAL mice, but significantly decreased levels in PCOC mice in both the Str and NAc following acute administration of cocaine or D1 agonist. We also found significantly higher levels of the BDNF precursor, pro-BDNF and one of its receptors, TrkB in the Str of PCOC mice. These results suggest a persistent up-regulation of molecules critical to D1 and BDNF signaling in the Str of adult mice exposed to cocaine in utero. These molecular adaptations may underlie components of the behavioral deficits evident in exposed animals and a subset of exposed humans, and may represent a therapeutic target for ameliorating aspects of the prenatal cocaine-induced phenotype.